Execution of Recognition of Grosse Documents Made Payable Notary - Rekowarno Rekowarno (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This study, entitled: Implementation of Execution of Deed of Acknowledgment of Debt Groose Created Notary, the problems of this study are 1) How is the execution of the Deed of Acknowledgment of Debt Groose made Notary? 2) What are the barriers and solutions in the execution of the Deed of Acknowledgment of Debt Groose made Notary? The method used in this research using normative juridical approach, which includes research principles of law, the legal systematics, synchronization of law, legal history and comparative law. The results using this method Sociological Juridical conclude that: 1) Execution of a debt recognition grosse deed as authentic deeds in the lending agreement, can only be carried out under the leadership of Chairman of the Court (court fiat) local. Not that grosse deed of acknowledgment of debt which includes the phrase,